The Effect of Interpersonal Communication and Learning Facilities on Learning Motivation in Elementary Schools, Sorong Regency - Rafiqatul Istiqomah; Oki Sandra Agnesa; Rusdin Rusdin (IAIN Surakarta, 2023)
This study aims to determine whether there is an influence from parents' interpersonal communication and learning facilities at home on students' learning motivation in elementary schools in Sorong Regency. This type of research is a quantitative correlational design. Using multiple linear regression statistical techniques with a significance level of 5%. Data was collected in class V at SD Inpres 15, Sorong Regency, with 53 students. The results showed a positive and significant influence between parents' interpersonal communication and learning facilities at home on students' learning motivation in elementary schools. This result is evidenced by the analysis results, namely the Sig value of 0.000 <0.05, which means the hypothesis is accepted. As for the results of the coefficient of determination, that is equal to 0.546 and shows that the influence of interpersonal communication between parents and learning facilities at home on student motivation is equal to 54.6%. So interpersonal communication and learning facilities positively affect students' learning motivation.